Ancient water bottle use and polycyclic aromatic hydrocarbon (PAH) exposure among California Indians: a prehistoric health risk assessment - Sabrina B. Sholts; Kevin Smith; Cecilia Wallin; Trifa M. Ahmed; Sebastian K. T. S. Wärmländer (BMC, 2017)
Abstract Background Polycyclic aromatic hydrocarbons (PAHs) are the main toxic compounds in natural bitumen, a fossil material used by modern and ancient societies around the world. The adverse health effects of PAHs on modern humans are well established, but their health impacts on past populations are unclear. It has previously been suggested that a prehistoric health decline among the native people living on the California Channel Islands may have been related to PAH exposure. Here, we assess the potential health risks of PAH exposure from the use and manufacture of bitumen-coated water bottles by ancient California Indian societies. Methods We replicated prehistoric bitumen-coated water bottles with traditional materials and techniques of California Indians, based on ethnographic and archaeological evidence. In order to estimate PAH exposure related to water bottle manufacture and use, we conducted controlled experiments to measure PAH contamination 1) in air during the manufacturing process and 2) in water and olive oil stored in a completed bottle for varying periods of time. Samples were analyzed with gas chromatography/mass spectrometry (GC/MS) for concentrations of the 16 PAHs identified by the US Environmental Protection Agency (EPA) as priority pollutants. Results Eight PAHs were detected in concentrations of 1-10 μg/m3 in air during bottle production and 50-900 ng/L in water after 2 months of storage, ranging from two-ring (naphthalene and methylnaphthalene) to four-ring (fluoranthene) molecules. All 16 PAHs analyzed were detected in olive oil after 2 days (2 to 35 μg/kg), 2 weeks (3 to 66 μg/kg), and 2 months (5 to 140 μg/kg) of storage. Conclusions For ancient California Indians, water stored in bitumen-coated water bottles was not a significant source of PAH exposure, but production of such bottles could have resulted in harmful airborne PAH exposure.